2006
DOI: 10.1523/jneurosci.0549-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Medial Versus Lateral Frontal Lobe Contributions to Voluntary Saccade Control as Revealed by the Study of Patients with Frontal Lobe Degeneration

Abstract: Deficits in the ability to suppress automatic behaviors lead to impaired decision making, aberrant motor behavior, and impaired social function in humans with frontal lobe neurodegeneration. We have studied patients with different patterns of frontal lobe dysfunction resulting from frontotemporal lobar degeneration or Alzheimer's disease, investigating their ability to perform visually guided saccades and smooth pursuit eye movements and to suppress visually guided saccades on the antisaccade task. Patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
92
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(110 citation statements)
references
References 69 publications
15
92
3
Order By: Relevance
“…Interestingly there was a positive correlation between antisaccade performance and the volume of a segment of the right frontal eye field using an unbiased voxel-based morphometric analysis of grey matter volume in their structural MRI images. 30 Findings in a recent study have shown that saccades are abnormal in FTD, reflecting reduced decision-making speed, and that these abnormalities related to atrophy of the left frontal eye field. In addition, patients with FTD had an increased incidence of early saccades, which may be due to reduced inhibition of primitive responses.…”
Section: Research Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly there was a positive correlation between antisaccade performance and the volume of a segment of the right frontal eye field using an unbiased voxel-based morphometric analysis of grey matter volume in their structural MRI images. 30 Findings in a recent study have shown that saccades are abnormal in FTD, reflecting reduced decision-making speed, and that these abnormalities related to atrophy of the left frontal eye field. In addition, patients with FTD had an increased incidence of early saccades, which may be due to reduced inhibition of primitive responses.…”
Section: Research Findingsmentioning
confidence: 99%
“…29,30 However, they were able to self-correct the antisaccade errors as well as controls, in contrast to patients with AD, corticobasal degeneration (CBD), and PSP. Interestingly there was a positive correlation between antisaccade performance and the volume of a segment of the right frontal eye field using an unbiased voxel-based morphometric analysis of grey matter volume in their structural MRI images.…”
Section: Research Findingsmentioning
confidence: 99%
“…Ocular motor abnormalities play an important role in differential diagnoses of Pick complex diseases [5,16,32,37]. Supranuclear gaze deficits among Pick complex diseases occur with PSP, CBD, and FTD.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies show slow saccades in PSP, especially in the vertical direction, even in early stages of the disease [32], a finding attributed to pathologic involvement of brainstem burst neurons [9,17,34]. Patients with CBD or FTD show relatively normal saccadic velocity but delayed initiation of saccades, which has been attributed to damage to cortical and subcortical structures for saccadic generation [5,32,37].…”
Section: Introductionmentioning
confidence: 99%
“…For example, AD patients could have simply forgotten the task instruction to saccade away from the target rather than saccade to it. Performance on antisaccade tasks have been linked to working memory (Mitchell, Macrae & Gilchrist, 2002) and measures of working memory have correlated with antisaccade performance in AD (Boxer et al, 2006). However, this theory remains controversial (Crawford, Parker, SolisTrapela & Mayes, 2011).…”
Section: Wwwintechopencommentioning
confidence: 99%